Moderasi Beragama: Optimalisasi Lembaga Sosial Ekonomi Keagamaan dengan Filantropy Islam - Latifah, Eny; Umah, Khurul Aimatul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
Background: Religious moderation is not only driven by the understandings and beliefs held by religious people but also actualization in the application of worship and mu'amalah that is built in a religion. Islam itself has philanthropy which is a reflection of actualizing the fulfillment of maqoshid sharia. The purpose: this study is to optimize the application of Islamic philanthropy in the Religious Socio-Economic institutions in increasing the value of religious moderation. The results: showed that religious moderation was not optimized by the Religious Socio-Economic Institution in the application of Islamic philanthropy which was reflected in the fulfillment of maqoshid sharia. Main Findings: The findings of this study indicate that socio-economic religious institutions should improve their strategies by developing strengths and turning threats into opportunities.